Displacement – based parametric study on the seismic response of gravity earth-retaining walls. Issue 80 (January 2016) - Deyanova, Manya; Lai, Carlo G.; Martinelli, Mario
Abstract: The essence of performance-based design of gravity earth-retaining structures lies in the estimation of the residual (i.e. permanent) displacements after a seismic event. The accomplishment of this task however can be very complicated due to two interacting phenomena: the coupled sliding and tilting rigid body motion of the wall on an inelastic base and the formation of failure surfaces in the soil backfill. In this study a large number of fully non-linear, time-history analyses of gravity retaining walls ( GRW ) were performed using advanced numerical modelling. Different types of soil parameters and varying wall geometry within a practical range were investigated. The influence of different ground motion parameters was discussed and the results were compared with some of the most common limit equilibrium Newmark׳s sliding block procedures, including the recommendations by Eurocode 8, Part 5[20] . Lastly, some recommendations for fast preliminary assessment of the seismic permanent displacements of GRW were provided. Highlights: Non-linear time-history analyses of gravity earth-retaining walls were performed. The results were compared with Newmark-based methods and guidelines by EN 1998-5. The influence of different ground motion intensity measures was discussed. The relation between permanent wall displacements and Arias intensity was investigated. Some recommendations for preliminary seismic design of gravity walls were given.